(untitled) (Research, Society and Development, 2022)
The urban planning of a municipality, when well carried out, results in an increase in the quality of life of citizens via several factors, such as better urban mobility, thermal comfort and even health benefits. Faced with the increase in urbanization and its impact on the environment, as well as the need to create public policies, the objective of this work was to evaluate the situation of urban planning in the Jardim Aeroporto neighborhood of the municipality of Itu, São Paulo, Brazil. An inventory and georeferencing of the tree individuals of 22 routes was carried out. To analyze the spatial distribution, the data were evaluated using the Kernel index and the degree of attention index. A total of 338 arboreal individuals distributed in 26 families and 47 species were sampled, with the most frequent species Murraya paniculata (L.) Jack, of exotic origin (15.68%). Only one route had a low level of attention, the others were between medium and high level of attention (n=21). In addition, there was a deficit of 1352 trees in the neighborhood. The results show that the roads of the Jardim Aeroporto neighborhood have an uneven distribution of arboreal individuals with a considerable amount of exotic species used in regional afforestation. The proximity between some trees and their distribution in risk areas in the city show how often there is no long-term urban planning, which can cause risks to the physical integrity of properties and citizens when associated with inadequate management of the species.